Knowledge Regarding HIV/AIDS among Nepalese Army - Roy, Roshan Kumar; Roy, Deepak Kumar; Ghimire, Sabal; Bist, Aayush; Maharaj, Anuranjan (Journal of Nepalgunj Medical College, 2022)
Introduction: A global pandemic threat HIV/AIDS is also matter of concern of developing countries like Nepal where the first case was identified in July 1988 and later became epidemic and then concentrated epidemic among risk group for HIV. Several studies reflected HIV is associated to many factors, Literacy and Socio-economic conditions being at the highest rank. Members of Nepal army are generally with less educational background and few with higher educational status are at higher post. Thus knowledge regarding HIV/AIDS among this group need to be assessed. Aims: The overall objective of our study was to assess knowledge regarding HIV/AIDS among Nepal army in Banke district. Methods: A Cross-sectional descriptive study with population size of 146 Army was performed which covered the entire population of Shree Shreemehar Army Camp in Banke, starting from 18th June to 27th August, 2018. A pre-tested questionnaire containing structural, semi-structural and open ended questions were made as data collection tool. All the soldiers in Army camp were interviewed after receiving consent as an ethical clearance. Results: All 146 Army of our study were aware about HIV/AIDS mainly via mass media (83.56%). 33 respondents still didn’t know about availability of its treatment. Misconception about its complete cure and vaccination was seen in 12 and 39 respondents respectively. 58 respondents were found knowing about the free health services by government. 141 respondents knew certain things about prevention. 28 respondents admitted of having multiple sex partners and only 24 among them used preventive measure. Conclusion: Though all the respondents of our study had known about HIV/AIDS still they had misconception regarding its treatment and prevention. Many respondents do not even know about the free health services of government. Few of them still don’t use preventive measure.